2020
DOI: 10.3389/fendo.2020.570846
|View full text |Cite
|
Sign up to set email alerts
|

Maternal High Fat Diet and Diabetes Disrupts Transcriptomic Pathways That Regulate Cardiac Metabolism and Cell Fate in Newborn Rat Hearts

Abstract: Background: Children born to diabetic or obese mothers have a higher risk of heart disease at birth and later in life. Using chromatin immunoprecipitation sequencing, we previously demonstrated that late-gestation diabetes, maternal high fat (HF) diet, and the combination causes distinct fuel-mediated epigenetic reprogramming of rat cardiac tissue during fetal cardiogenesis. The objective of the present study was to investigate the overall transcriptional signature of newborn offspring exposed to maternal diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 109 publications
(163 reference statements)
1
18
0
Order By: Relevance
“…It is well known that offspring of diabetic mothers develop responsive hyperinsulinemia in utero, which may "program" mitochondrial dysfunction including oxidative phosphorylation and viability. In our own studies, we have shown disruptions in cardiac insulin signaling pathways and relative insulin resistance in myocardium of offspring exposed to LGDM and maternal HF diet [11], so it is plausible that the hyperinsulinemia in our PGDM-exposed offspring is driving the mitochondrial effects shown here.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…It is well known that offspring of diabetic mothers develop responsive hyperinsulinemia in utero, which may "program" mitochondrial dysfunction including oxidative phosphorylation and viability. In our own studies, we have shown disruptions in cardiac insulin signaling pathways and relative insulin resistance in myocardium of offspring exposed to LGDM and maternal HF diet [11], so it is plausible that the hyperinsulinemia in our PGDM-exposed offspring is driving the mitochondrial effects shown here.…”
Section: Discussionmentioning
confidence: 68%
“…Finally, studies should further investigate whether developmentally programmed changes in mitochondria are inherited or acquired following exposure to in utero conditions. Reflecting metabolic memory mentioned above, we have previously found distinct, epigenetic signatures with maternal LGDM and HF diet that vary by solo and combination exposure [11,12]. The work of Miller and Orchard disputes the concept that short-term exposure to hyperglycemia alone causes disease attributed to metabolic memory; disease can instead be attributed to cumulative hyperglycemia exposure [57].…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…A transcriptomic study performed in neonatal heart from dams treated with a combination of high-fat diet and STZ at day 14 of pregnancy, showed many changes in key genes of metabolic cardiac pathways. Among them, a downregulation of fibroblast growth factor ( FGF ), which in turn downregulates PI3K/AKT pathway activation that lead to increased glycogen synthase kinase 3 β ( GSK3β ) and peroxisome proliferator-activated receptor gamma coactivator alpha ( PGC1α ; Preston et al, 2020 ). PI3K/AKT is an insulin sensitive pathway that modulates metabolic pathways as gluconeogenesis (modulated by GSK3β) and mitochondrial function and biogenesis (modulated by PGC1α), between others.…”
Section: Animal Studiesmentioning
confidence: 99%